UPAYA GURU PENDIDIKAN AGAMA ISLAM DALAM MENANAMKAN NILAI KARAKTER KEPEDULIAN SOSIAL PADA SISWA SMA NEGERI 2 MALANG - Adi Kuswandi; Rosichin Mansur; Siti Masyruhah (VICRATINA, 2022)
Character education is an important thing that must be instilled in students, the purpose of character planting is to print the next generation of noble character, one of which is the character of social care. The development of the digital world affects the embedded character of social care for students. For this reason, teachers must have steps in planting social care characters. The author conducted research on the programs, strategies and results of the efforts of Islamic religious education teachers in instilling social care character values in SMA Negeri 2 Malang. In data collection techniques, researchers used interviews, observation and documentation. The results of this study focus on programs, strategies and results of PAI teachers' efforts in instilling social care characters in SMA Negeri 2 Malang.